2022
DOI: 10.1016/j.pmedr.2021.101691
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between personality traits and health behavior among working women in Japan

Abstract: Considering personality traits is effective for cultivating health promotion habits. Therefore, individualized interventions that account for personality traits would be more beneficial for modifying health behaviors. The present study describes the relationship between personality traits and health behaviors among working women compared with non-working women in Japan. Secondary analysis was conducted using nationally representative data from the Japanese Household Panel Survey (JHPS/KHPS). In the 2019 wave, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…With regard to extraversion, previous studies have reported that women are more extraverted than men 30 , 40 . It has also been reported that higher extraversion is associated with desirable physical activity habits among women 57 . These previous findings support the association between perceived health competence and agreeableness among women revealed in the present study.…”
Section: Discussionmentioning
confidence: 92%
“…With regard to extraversion, previous studies have reported that women are more extraverted than men 30 , 40 . It has also been reported that higher extraversion is associated with desirable physical activity habits among women 57 . These previous findings support the association between perceived health competence and agreeableness among women revealed in the present study.…”
Section: Discussionmentioning
confidence: 92%
“…Positive psychosocial traits provide a variety of benefits for medical patients, including improvements in health-related maintenance, treatment compliance, and overall wellbeing (5)(6)(7)(8)(9)(10)(11). Grit, defined as passion and perseverance for longterm goals, offers potential advantages to the cancer population, as it denotes an increased ability to overcome adversity (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%